Macroeconomic Policy in a Two-Party System as a Repeated Game - Alesina, Alberto (Quarterly Journal of Economics, 1987)
This paper considers the interaction of two parties with different objectives concerning inflation and unemployment and rational and forward-looking wage-setters. If discretionary policies are followed, an economic cycle related to the political cycle results in equilibrium. This cycle is significantly different from the traditional "political business cycle." Reputational mechanisms due to the repeated interaction of the two parties and the public or commitments to a common policy rule can improve upon the discretionary outcome by reducing or eliminating the magnitude of the economic fluctuations.